2016
DOI: 10.1177/0149206316632057
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Negative Workplace Gossip: A Self-Consistency Theory Framework

Abstract: We present and test a self-consistency theory framework for gossip: that perceived negative workplace gossip influences our self-perceptions and, in turn, this influences our behaviors. Using supervisor-subordinate dyadic time-lagged data (n = 403), we demonstrated that perceived negative workplace gossip adversely influenced target employees’ organization-based self-esteem, which, in turn, influenced their citizenship behavior directed at the organization and at its members. Moreover, by integrating victimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
244
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(254 citation statements)
references
References 107 publications
(187 reference statements)
8
244
2
Order By: Relevance
“…As per Kurland and Pelled (2000), the gossip must take place within a social setting (organization), it must be targeted towards individuals within the organization, must be evaluative in nature, and the target or victim should be known to the gossiper, and only the gossiper knows the subject of gossip. In addition, some scholars have suggested a vital component of the gossip web: that the gossip usually takes place in the absence of the victim, thus making it difficult for the victim to establish the source of the gossip or to substantiate the authenticity of the contents of the gossip (Wu et al, 2016). However, with supervisor negative or positive gossip, the web is clear: it is the supervisor gossiping the subordinates regarding their work attributes and behaviors, or performance (Kuo et al, 2015).…”
Section: Literature Review Supervisor Workplace Gossipmentioning
confidence: 99%
See 2 more Smart Citations
“…As per Kurland and Pelled (2000), the gossip must take place within a social setting (organization), it must be targeted towards individuals within the organization, must be evaluative in nature, and the target or victim should be known to the gossiper, and only the gossiper knows the subject of gossip. In addition, some scholars have suggested a vital component of the gossip web: that the gossip usually takes place in the absence of the victim, thus making it difficult for the victim to establish the source of the gossip or to substantiate the authenticity of the contents of the gossip (Wu et al, 2016). However, with supervisor negative or positive gossip, the web is clear: it is the supervisor gossiping the subordinates regarding their work attributes and behaviors, or performance (Kuo et al, 2015).…”
Section: Literature Review Supervisor Workplace Gossipmentioning
confidence: 99%
“…Supervisor negative gossip occurs when supervisor discuss their subordinates concerning their decline in job performance, lethargic workplace attitudes and interpersonal relations as well as their level of organization citizen behavior (Wu et al, 2016). Subordinates desire positive supervisor gossip to negative one (Baumeister et al, 2004), since they perceive it as a form of performance feedback from the supervisor (Brady et al, 2017), while negative supervisor is perceived as a form of sanction which increases employee workplace stress, negative affectivity, and reduced employee leader member exchange…”
Section: Literature Review Supervisor Workplace Gossipmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, extant contributions have shown mixed results: while some have demonstrated that negative news is more likely to be shared (e.g., Hornik, Satchi, Cesareo, & Pastore, 2015), others have highlighted that people prefer to pass on positive information (e.g., Berger & Milkman, 2012). Further, most research examines gossip valence as being positive vs. negative (e.g., Ellwardt, Labianca, & Wittek, 2011;Wu et al, 2016), thereby leaving room for studying further valenced nuances, such as the gossip maliciousness. In this regard, existing works on malicious gossip have proposed theoretical arguments (Wert & Salovey, 2004), applied discourse analysis (Guendozi, 2001), developed surveys (Lyons & Hughes, 2015), implemented multiagent models (Smith, 2014) or observational techniques (Low, Frey, & Brockman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While the former is captured by looking at the gossip valence, being both positive vs. negative and malicious vs. non-malicious, the latter is analyzed by considering gossip as a relational process involving a gossiper, a receiver, and a gossip target (Foster, 2004;Wu et al, 2016). In particular, we study the social transmission of gossip by incorporating in our model both the target-receiver interpersonal closeness and the sender-receiver relationship by focusing on whether the receiver might or might not be able to verify the truthfulness of the gossip.…”
Section: Introductionmentioning
confidence: 99%